Presidential leadership politics and policy making - Edwards, George C., III; Mayer, Kenneth R.; Wayne, Stephen J. (Rowman & Littlefield, 2018)
With a focus on presidential leadership, the authors address the capacity of chief executives to fulfill their tasks, exercise their powers, and utilize their organizational structures to affect the output of government. The authors examine all aspects of the presidency in rich detail, including the president’s powers, presidential history, and the institution of the presidency. Guiding their analysis is their unique contrast between two broad perspectives on the presidency—the constrained president (“facilitator”) and the dominant president (“director”)—making the text a perennial favorite for courses on the presidency.